Development of Chemically Defined Media Reveals Citrate as Preferred Carbon Source for Liberibacter Growth - Cruz-Munoz, Maritsa; Petrone, Joseph R.; Cohn, Alexa R.; Munoz-Beristain, Alam; Killiny, Nabil; Drew, Jennifer C.; Triplett, Eric W. (Frontiers in Microbiology, 2018)
Liberibacter crescens is the closest cultured relative of four important uncultured crop pathogens. Candidatus L. asiaticus L. americanus, and L. africanus are causal agents of citrus greening disease, otherwise known as huanglongling (HLB). Candidatus L. solanacearum is responsible for potato Zebra chip disease. Cultures of L. crescens grow slowly on BM-7 complex medium, while attempts to culture the Ca. Liberibacter pathogens in BM-7 have failed. Developing a defined medium for the growth of L. crescens will be useful in the study of Liberibacter metabolism and will improve the prospects for culturing the Ca. Liberibacter pathogens. Here, M15 medium is presented and described as the first chemically defined medium for the growth of L. crescens cultures that approaches the growth rates obtained with BM-7. The development of M15 was a four step process including: 1) the identification of Hi-Graces Insect medium (Hi-GI) as an essential, yet undefined component in BM-7, for the growth of L. crescens, 2) metabolomic reconstruction of Hi-GI to created a truly defined version of this medium which was evaluated for the growth of L. crescens cultures, 3) the discovery of citrate as the preferred carbon and energy source for L. crescens growth, and 4) the demonstration of culture growth in M15 medium though 14 generations. The composition of M15 medium includes inorganic salts as in the Hi-GI formula, amino acids derived from the metabolomic analyses of Hi-GI, and a 10-fold increase in vitamins compared to the Hi-GI formula, with exception choline chloride, which was increased 5000-fold in M15. Since genome comparisons of L. crescens and the Ca. Liberibacter pathogens show that they are very similar metabolically. Thus, these results imply citrate and other TCA cycle intermediates are main energy sources for these pathogens in their insect and plant hosts. Thus, strategies to reduce citrate levels in the habitats of these pathogens may be effective in reducing Ca. Liberibacter pathogen populations thereby reducing symptoms in the plant host.